PENGEMBANGAN MEDIA SCRABBLE GAMES BERBASIS CASE METHOD DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH DASAR - Sari, Elsa; Sirait, Albert Pauli; Simanjuntak, Eva Betty; Sarjani, Tiarnita Maria; Ambarita, Dody Feliks Pandimun (Universitas Negeri Medan, 2025)
This study aims to develop a Scrabble Games-based learning media integrated with the Case Method to improve students’ English vocabulary mastery in the fourth grade of elementary school. The research employed a Research and Development (R&D) method using the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 17 fourth-grade students at SDN 040541 Suka. Data were collected through interviews, observations, tests, and questionnaires, then analyzed descriptively and using N-Gain analysis. The results showed that: (1) the media was declared feasible based on expert validation in terms of content, language, and media design; (2) the media was considered very practical by teachers and students; and (3) the use of Scrabble Games media was proven effective in enhancing students’ vocabulary, with an N-Gain score of 0.56, categorized as moderate. These findings indicate that Scrabble Games media based on the Case Method is valid, practical, and effective for supporting vocabulary learning in elementary English education.